Profiling bile acid composition in bile from mice of different ages and sexes - Liu, Jiajian; Zhao, Qing; Qu, Chun; Ge, Kun; Li, Yang; Jia, Wei; Zhao, Aihua (Frontiers in Physiology, 2025)
IntroductionBile BA profiling is important for understanding the pathogenetic mechanisms underlying gallbladder and gastrointestinal diseases. Until now, bile BAs have been explored mainly in adult male mice. However, sex- and age-related variations in the bile BA composition of normal experimental mice remain poorly characterized.MethodsBAs in bile from healthy, age-and sex-matched mice (8-week-old and 60-week-old) were quantified using ultra-performance liquid chromatography coupled with triple-quadrupole mass spectrometer (UPLC-TQ-MS). The bile BA profiles were comprehensively compared across different ages and sexes, along with comparisons within the same sex at different ages.ResultsTotal BAs (TBAs) in female mice were higher than those in male mice at both ages, although total BAs and BA profiles were similar between the two ages. High concentrations of BAs contributed significantly to the observed sex differences at both ages. Notably, both high- and low-concentration BAs were regulated with increasing age in male mice, while only low-concentration BAs were modulated with age in female mice. A remarkable sex difference in total cholesterol (TC) was also observed, along with a significant negative association between TC and BA profiles.ConclusionThe findings demonstrate that bile BA profiles differ markedly with both sex and physiological age in commonly used normal laboratory mice, suggesting the need to consider for physiological differences related to sex and age when selecting suitable animals for pharmaceutical research and for mechanistic studies.